Job satisfaction as a mediator of the relationship between transformational leadership practice and commitment to organizational change among community college instructors - Ab Rahman, Rosmilawati; Mat Rashid, Abdullah (EuroJournals, 2018)
This study aims to identify the relationship between the dimensions of transformational leadership practice with commitment to organizational change among community college instructors. Furthermore, this study also examines the role of job satisfaction as mediator in the relationship between transformational leadership with commitment to organizational change. The total of 330 community college instructors involved as respondents in the study and data was gathered using a questionnaire where the directors’ transformational leadership practices were measured using the Principle Leadership Questionnaire (PLQ). Instructors’ job satisfaction was measured using the Job Satisfaction Survey (JSS) and the commitment to organizational change among instructors’ was measured using Commitment to Change Scale (C2CS). The finding shows that there is a significant positive relationship between all dimensions of transformational leadership practice which is examined with commitment towards organizational change. Meanwhile, the results of the mediator analysis found that job satisfaction partially mediated the relationship between of transformational leadership practice with commitment to organizational change among instructors’.